Recognized Occupational Diseases in Italy’s Friuli-Venezia Giulia and Liguria Regions (2010-2021) - Larese Filon, Francesca; Granzotto, Jessica; Bignotto, Antonio; Alessandrini, Barbara; Barbina, Paolo; Rui, Francesca (La Medicina del Lavoro, 2023)
Background: The study of recognized occupational diseases trend is important to understand the preventive approach needed in the future, however, while numbers of occupational diseases are available on web, data on incidence are missing. The aim of our study was to analyze the trend and the incidence rate ratio (IRR) of recognized occupational diseases in Italy, in Friuli-Venezia Giulia region (FVG) and Liguria region from 2010 to 2021. Methods: Numbers of recognized occupational diseases by the Italian National Insurance for Occupational Diseases (INAIL) were analyzed and incidence were calculated considered the total number of workforces in the area. A Poisson regression model was used to estimate incidence trends. Results: FVG region presented a higher incidence of all occupational diseases compared to Italy and to Liguria in the period considered. The overall incidence in 2019 was 175, 91.8 and 108 cases for 100,000 workers, for FVG, Liguria and Italy respectively. Musculoskeletal disorders (MSDs) were the majority of occupational diseases with 100, 51 and 82.8 cases per 100,000 workers, in FVG, Liguria and Italy, respectively. Incidence of occupational cancers was 16, 10 and 4.9 cases per 100,000 workers, in FVG, Liguria and Italy, respectively. The annual change of incidence from 2010 to 2019 was positive for MSDs (IRR 1.06; 95%CI 1.06 to 1.07) and decreasing for the other causes in Italy. In FVG region the trend was positive for MSDs (IRR 1.05;95%CI 1.04 to 1.06), for respiratory diseases (IRR 1.03; 95%CI 1.00 to 1.05) and pleural plaques (IRR 1.03; 95%CI 1.00 to 1.06). In Liguria the trend was positive for MSDs (IRR 1.17; 95% CI 1.15-1.19) and for pleural plaques (IRR 1.07; 95%CI 1.03-1.12). Stable trends were found for cancers. Declining trend was shown for noise induced hearing loss and skin diseases. Conclusions: FVG region presented a higher incidence of recognized occupational diseases compared to Liguria region and Italian data. Results that can be explained by a higher propensity of claiming for occupational diseases in workers, mainly for MSDs disorders. For cancers and asbestos-related diseases the higher incidence can be attributable to high exposure to asbestos in FVG and Liguria workers mainly in shipyard and dock activities.